Now presenting the undistinguished achievement award: how relative standing creates exceptional outcomes from recognizing unexceptional sales associates. Issue 3 (3rd July 2022) - Harding, R. Dustin; Murdock, Mitchel R.
Abstract: Companies frequently recognize overall top-performing salespeople in order to inspire those not recognized to exhibit greater performance and commitment to the company. This research investigates if, contrary to common industry practice, there are cases where recognition of unexceptional performers, those whose lower-tier performance is only slightly above the unrecognized, can have a positive effect on the performance and retention of novice (i.e., new or inexperienced) salespeople. In one field experiment with a company that has annual revenues over two billion dollars and two lab experiments, the authors demonstrate that highlighting the achievements of salespeople whose performance is only slightly better than novices can be more effective at increasing performance and retention rates among novices than highlighting salespeople with far better performance. The enhancements include higher activity rates (Study 1) and company commitment (Study 2; Study 3). This research demonstrates the role relative standing plays in creating effective recognition strategies and refutes a commonly practiced recognition approach.